(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article focuses on an assumption of using interactive methods, which can be applied for ESP students. Therefore, the researcher discusses outcomes of interactive methods, conducted lessons, and offers not only suggestions for organizing effective classes, but also presents a variety of activities for success of teaching logistics terms to ESP students.